2010
DOI: 10.2478/s11534-010-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Series solution of unsteady free convection flow with mass transfer along an accelerated vertical porous plate with suction

Abstract: The problem of unsteady free convection flow is considered for the series solution (analytic solution). The flow is induced by an infinite vertical porous plate which is accelerated in its own plane. The series solution expressions for velocity field, temperature field and concentration distribution are presented. The influence of important parameters is seen on the velocity, temperature, concentration, skin friction coefficient and temperature gradient with the help of graphs and tables. Convergence is also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The application of HAM was considered by Nassar [13], as he suggested that by using HAM the solution of the nonlinear Poisson-Boltzmann equation for semiconductor devices was extremely good analytical approximations. Zaman [14] studied the series solution of stagnation point flow with mass transfer along an accelerated vertical porous plate with suction by means of HAM and he found out an exact analytical solution. Also Zaman, H. [15] proposed exact analytic series solution for heat transfer from a continuous surface in a parallel free stream of viscoelastic fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The application of HAM was considered by Nassar [13], as he suggested that by using HAM the solution of the nonlinear Poisson-Boltzmann equation for semiconductor devices was extremely good analytical approximations. Zaman [14] studied the series solution of stagnation point flow with mass transfer along an accelerated vertical porous plate with suction by means of HAM and he found out an exact analytical solution. Also Zaman, H. [15] proposed exact analytic series solution for heat transfer from a continuous surface in a parallel free stream of viscoelastic fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a pressure gradient and Hall current on the flow are also taken in to account. The complex analytical solution for the non-linear problem is found by using the homotopy analysis method (HAM) [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Keeping this all in view, in the present paper, the authors envisage studying the time-dependent Couette flow of incompressible non-Newtonian Eyring-Powell model with porous walls. The resulting unsteady problem is solved by means of homotopy analysis method (HAM) [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], which is very powerful and efficient in finding the analytic solutions for a wide class of nonlinear differential equations. The method gives more realistic series solution that converges very rapidly in physical problems.…”
Section: Introductionmentioning
confidence: 99%